India, Uttarakand Disaster, June 2013 : Joint Rapid Damage and Needs Assessment Report - World Bank (New Delhi, 2014)
The State of Uttarakhand experienced an unprecedented high rainfall between June 15 and 17, 2013 that resulted in flash floods and landslides within the State. The continuous rain disrupted normal life resulting in a total of 580 human lives being lost, more than 4,000 persons missing and over hundred thousand pilgrims being stranded. This event has affected over 900,000 people in Uttarakhand this year. The numerous landslides and toe erosion by the sediment loaded rivers caused breaching of roads and highways at many locations and washed away several bridges; disrupting traffic and telecommunication links within the state. The Government of Uttarakhand (GoU) launched a massive emergency rescue and evacuation operation with assistance from the Indian Army, Indian Air Force (IAF), Indo-Tibetan Border Police (ITBP), the National Disaster Response Force (NDRF) and the local Police evacuating more than 110,000 people from these flood affected areas. The State Government continues to ensure that there is no shortage of food and other essential supplies, especially for communities in areas with connectivity problems. Additionally, doctors and paramedics were deployed in the disaster affected areas to provide medical services. This report presents an assessment of the physical damages with a sector-wise impact of the disaster, reconstruction needs and preliminary estimates specifically with regards to infrastructure, housing, services and livelihood.